2021
DOI: 10.3389/fmicb.2021.699913
|View full text |Cite
|
Sign up to set email alerts
|

Aerobactin-Mediated Iron Acquisition Enhances Biofilm Formation, Oxidative Stress Resistance, and Virulence of Yersinia pseudotuberculosis

Abstract: Aerobactin is a citrate-hydroxamate siderophore that is critical for the virulence of pathogenic enteric bacteria. However, although the aerobactin-producing iucABCD-iutA operon is distributed widely in the genomes of Yersinia species, none of the pathogenic Yersinia spp. was found to produce aerobactin. Here, we showed that the iucABCD-iutA operon in the food-borne enteric pathogen Yersinia pseudotuberculosis YPIII is a functional siderophore system involved in iron acquisition. The expression of the operon w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 79 publications
(99 reference statements)
0
17
0
1
Order By: Relevance
“…It is reported that PiuA and PirA and their homologs in the TBDRs of A. baumannii and P. aeruginosa are involved in the uptake of siderophore-beta-lactam drug conjugates ( Luscher et al, 2018 ). Several proteins and genes related to acquisition of iron ions, iron uptake systems and ferric aerobactin receptors have been reported to promote biofilm formation ( Kang and Kirienko, 2018 ; Li et al, 2021 ). It was found in our study that iron uptake system component efeO , tonB-dependent receptor fecA , and ferric iron ABC transporter fbpA were down-regulated in both proteomic or transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that PiuA and PirA and their homologs in the TBDRs of A. baumannii and P. aeruginosa are involved in the uptake of siderophore-beta-lactam drug conjugates ( Luscher et al, 2018 ). Several proteins and genes related to acquisition of iron ions, iron uptake systems and ferric aerobactin receptors have been reported to promote biofilm formation ( Kang and Kirienko, 2018 ; Li et al, 2021 ). It was found in our study that iron uptake system component efeO , tonB-dependent receptor fecA , and ferric iron ABC transporter fbpA were down-regulated in both proteomic or transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The production of aerobactin has been associated with increased virulence and relapse episodes of urinary tract infections [ 66 , 67 ]. Under iron-limiting and oxidative stress conditions, aerobactin has increased biofilm formation and hydrogen peroxide resistance respectively [ 68 ]. When the whole-genome sequence was analyzed with PathogenFinder [ 69 ], E. coli 1000C-3 matched 663 pathogenic families, resulting in a pathogen probability of 0.919.…”
Section: Resultsmentioning
confidence: 99%
“…ABC transporter complex FhuCDB involved in Fe 3 + ‐hydroxamate import, responsible for energy coupling to the transport system (Schultz‐Hauser et al, 1992), and genes ddhABCD for the conversion of glucose‐1‐phosphate to CDP‐4‐keto‐3,6‐dideoxy‐ d ‐glucose (Pacinelli et al, 2002), were absent in V. echinoideorum compared to V. lentus . While, the aerobactin‐producing iucABCD‐iutA operon was inserted in the genome of V. kanaloae compared to V. toranzoniae , aerobactin is a citrate‐hydroxamate siderophore that is important for the virulence of pathogenic enteric bacteria (Li et al, 2021).…”
Section: Resultsmentioning
confidence: 99%